KAEDAH MENYELESAIKAN PERTIKAIAN KELUARGA DALAM MASYARAKAT MELAYU: ZAMAN PRA DAN PASCA KOLONIAL - Azahari, Raihanah (Jurnal Syariah, 2019)
Informal dispute resolution, mainly mediation and conciliation, has long been practised by the Malay Muslim communities as part and parcel of their cultural and religious traditions. In the pre-colonial period the family played the main role in conflict resolution, usually assisted by elderly members of the extended family circle. As in many traditional societies, the family was recognized as the main instrument of social control throughout the individual’s life span. Should any individual be involved in a conflict, especially in an intra-family dispute, it was responsibility of the family elders to handle the matter. If the conflict cannot be resolved or become protracted, village elders or appointed leaders are often called on to assist the family. The former are consulted and decisions respected due to their wisdom, standing in society and experience as mediators. However, socio-economic changes occurring over the last several decades have transformed the nature and role of family relationships, limiting the existence and influence of the the extended family system. Gradually, traditional mediation and conciliation were replaced by modern adjudication as the resort almost all forms of interpersonal conflict in present-day Malay Muslim society.